Karma and rebirth in Hinduism - Medhananda, Swami (Cambridge elements. Elements in global philosophy of religion, 2025)
This Element provides an argumentative introduction to the doctrines of karma and rebirth in Hinduism. It explains how various Hindu texts, traditions, and figures have understood the philosophical nuances of karma and rebirth. It also acquaints readers with some of the most important academic debates about these doctrines. The Element's primary argumentative aim is to defend the rationality of accepting the truth of karma and rebirth through a critical examination of an array of arguments for and against these doctrines. It concludes by highlighting the relevance of karma and rebirth to contemporary philosophical debates on a variety of issues.